Does Child Labor Lead to Vulnerable Employment in Adulthood? Evidence for Tanzania - Sara Burrone; Gianna Claudia Giannelli (Institute of Labor Economics (IZA), 2019)
This paper investigates the relationship between child labor and status in employment in adulthood. We aim to contribute to the literature that focuses on the obstacles to the formation early in life of the skills that allow people to avoid vulnerability. Using the panel data survey for the Kagera region of Tanzania, we select children who were 7 to 15 years old in the 1990s and follow up with them in the first decade of the 2000s to study the consequences of child labor on adult employment. We estimate fixed effects linear probability models. We find that child labor is associated with vulnerable employment in adulthood. Negative adult employment effects arise when children who are younger than 11-12 work more than ten to twenty hours per week. This result is driven by girls. As for types of child labor, work on the household farm shows the largest negative effects.
Keywords: J13; J21; J24; 330; child labor; vulnerable employment; unpaid work; women's employment in developing countries; Kagera region of Tanzania; Africa